Efficacy and Safety of Cetuximab Plus Cisplatin Alone or in Combination With Paclitaxel in Patients With Head and Neck Squamous Cell Carcinoma: A Randomized Trial. (23rd May 2021) - Zheng, Yanqing; Dou, Huiqin; Li, Qingchen; Sun, Ying; Wang, Yanchao; Zhang, Wendong
Objectives: The aim of this study was to assess the clinical usefulness of cetuximab and cisplatin alone or in combination with paclitaxel as the first-line treatment of patients with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC). Methodology: Three hundred patients with confirmed HNSCC from 20 different hospitals were included in this study. Patients in group I underwent a 2-hour infusion of 400 mg/m 2 cetuximab (day 1), followed by a 1-hour infusion of 250 mg/m 2 cetuximab weekly and 1-hour infusion of 100 mg/m 2 cisplatin (days 1 and 21) per treatment cycle. Patients in group II were treated with a combination of cetuximab, cisplatin, and paclitaxel. Patients received 6 cycles of 175 mg/m 2 paclitaxel given on days 1 and 21. The primary outcome of the study was progression-free survival (PFS); overall survival (OS) and objective response rate (ORR) were the secondary endpoints. Results: The median PFS was 5 months and 8 months for patients in groups I and II, respectively (HR, 0.93; 95% CI, 0.85–1.78; P > 0.05). Similarly, we found no significant differences in OS between the 2 groups (median OS, 13 vs. 11 months, respectively; HR, 0.67; 95% CI, 0.42–1.43; P = 0.198). Moreover, we observed no significant difference in ORR between the 2 groups (ORR, 63.3% vs 69.9%, respectively; HR, 0.87; 95% CI, 0.36–1.67; P = 0.231). Conclusions: The combination of paclitaxel with cetuximab and cisplatin did not improve patient outcomes compared to cetuximab plus cisplatin alone. Therefore, the 2-drug regimen could be used as first-line treatment in patients with recurrent or metastatic HNSCC.